2019
DOI: 10.1186/s13073-019-0691-1
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals a high prevalence of BRCA1 and BRCA2 founder variants in a diverse population-based biobank

Abstract: BackgroundPathogenic variants in BRCA1 and BRCA2 (BRCA1/2) lead to increased risk of breast, ovarian, and other cancers, but most variant-positive individuals in the general population are unaware of their risk, and little is known about prevalence in non-European populations. We investigated BRCA1/2 prevalence and impact in the electronic health record (EHR)-linked BioMe Biobank in New York City.MethodsExome sequence data from 30,223 adult BioMe participants were evaluated for pathogenic variants in BRCA1/2. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 67 publications
8
95
0
Order By: Relevance
“…For example, our group and others have found that screening unselected cohorts for pathogenic/likely pathogenic BRCA1/2 variants can lead to improved ascertainment of individuals with these variants, 50% of whom did not have a personal or family history indicating their increased cancer risk. 1 3 Further, genomic screening programs can identify individuals with early-onset cancers 4 and improve medication management in individuals with high cholesterol levels. 5 …”
Section: Introductionmentioning
confidence: 99%
“…For example, our group and others have found that screening unselected cohorts for pathogenic/likely pathogenic BRCA1/2 variants can lead to improved ascertainment of individuals with these variants, 50% of whom did not have a personal or family history indicating their increased cancer risk. 1 3 Further, genomic screening programs can identify individuals with early-onset cancers 4 and improve medication management in individuals with high cholesterol levels. 5 …”
Section: Introductionmentioning
confidence: 99%
“…The Bio Me Biobank is an ongoing electronic health record (EHR)-linked biorepository in New York City. Over 55,000 Bio Me participants have been enrolled since 2007, predominantly through unselected medicine and specialty ambulatory care practices across the Mount Sinai Health System (MSHS) [ 5 , 31 ]. A subset of Bio Me participants have undergone exome sequencing and genotyping through a collaboration with the Regeneron Genetics Center [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over 55,000 Bio Me participants have been enrolled since 2007, predominantly through unselected medicine and specialty ambulatory care practices across the Mount Sinai Health System (MSHS) [ 5 , 31 ]. A subset of Bio Me participants have undergone exome sequencing and genotyping through a collaboration with the Regeneron Genetics Center [ 5 ]. In October 2018, the Bio Me protocol and consent were modified to include the option for participants to receive clinically confirmed, medically actionable genomic results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations